Effects of storage methods, storage duration and different geographical locations on quality of stored wheat (Triticum aestivum) in Sindh, Pakistan - Chattha, Shakeel Hussain; Lee, Teang Shui; Mirani, Benish Nawaz; Che Man, Hasfalina (International Network for Natural Sciences, 2014)
Wheat grain stored in traditional structures was sampled from four selected districts of Sindh from July 2013 to July 2014 at 3 months interval and was analysed for quality deterioration over time. The maximum ambient temperature was noted in district Shaheed Benazir Abad followed by Sukkur, Hyderabad and Badin districts whereas the maximum relative humidity was observed in district Badin followed by Sukkur, Shaheed Benazir Abad and Hyderabad. The grain temperature followed the pattern of the ambient temperature and was higher than the ambient temperature during whole storage period. Moisture content, insect infestation and aflatoxin content showed an increasing pattern with prolonged storage. Among the storage structures the lowest grain temperature and moisture content were recorded in earthen bin whereas the highest in room structure and bulk covered, respectively. The highest percentage of insect infestation and aflatoxin content was observed in grains stored in room structure whereas, maximum test weight and seed germination capacity were recorded in grain samples taken from earthen bin. The levels of aflatoxins detected in stored wheat from survey districts were far above the internationally accepted standards and that the farmers were at risk of ill health through consuming contaminated wheat. It was concluded that the quality of wheat stored using traditional storage methods in surveyed districts was low and that these storage methods were inadequate for protecting stored wheat from pests. Modification of these structures or replacing with better designed storage structures can stop deterioration and improve grain quality and storability.